Facile preparation of W5O14 nanosheet arrays with large crystal channels as high-performance negative electrode for supercapacitor. (10th January 2020) - Huang, Chuqiang; Zhu, Qiancheng; Zhang, Wei; Qi, Pengcheng; Xiao, Qin; Yu, Ying
Abstract: The crystal structure of WO3 is orderly arranged with WO6 structure, possessing crystal channels for convenient charge transfer and ion diffusion. Using effective strategies to broaden the crystal channels of this materials can improve the charge transfer and ion diffusion. In this work, we have facilely utilized a sample hydrogenation method to introduce distorted WO6 structures into the crystal of tungsten oxide, which leads to the crystal reconstruction and W5 O14 formation with large crystal channels. Due to the existence of large crystal channels, as-fabricated W5 O14 nanosheet arrays achieve a high specific capacitance of 1352 mF cm −2 (524 F g −1 ) at current density of 1 mA cm −2, much higher than that of WO3 . In addition, W5 O14 nanosheet arrays also exhibit good stability with 84% capacitance retention after 4000 cycles. Finally, the high energy and power density of the asymmetric full supercapacitor W5 O14 //RuO2 device shed light on the potentially commercial application of W5 O14 . Graphical abstract: Image 1 Highlights: W5 O14 with large crystal channels as negative electrode was investigated. Effect of large crystal channels on ion diffusion was explored. High specific capacitance of 1352 mF cm −2 (524 F g −1 ) was obtained. W5 O14 //RuO2 device shed light on the potentially commercial application of W5 O14 .